The Effect of Tax Treaties on Foreign Investment Receipts in Indonesia - Novanda Lutfi; Puji Rahayu; Moch.wahyudi (LP2M IAIN Palopo, 2026)
The purpose of this study is to assess how the Tax Treaty (x) affects Indonesia's (Y) foreign investment receipts. All countries that have a Tax Treaty or double tax avoidance agreement with Indonesia constitute the population of this study, and 26 countries were selected as examples using purposive sampling inclusion criteria. The direct linear analysis method was used for this study. Secondary data is used in the data collection approach of this study, namely the documentation method. Official publications from government agencies provide data, which are then entered into the data panel covering the years 2020–2024 and analyzed using IBM SPSS software. According to the findings of this study, the Tax Treaty has little impact on foreign investment in Indonesia. The regression findings, which resulted in a significance value of 0.102, which is higher than 0.05, support this conclusion. As a result, this study shows that the Tax Treaty has little influence on the movement of foreign investment into Indonesia during the study. Based on these findings, foreign investors choose to invest in Indonesia for a variety of reasons, not just because of the Tax Treaty law.